2022
DOI: 10.1007/s10147-022-02161-5
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR-17 predicts adverse prognosis and disease recurrence for acute myeloid leukemia

Abstract: Background The clinical significance of miR-17 in patients with acute myeloid leukemia (AML) remains unknown. Methods Real-time quantitative reverse transcription-polymerase chain reaction (qPCR) was performed to detect the miR-17 expression in 115 de novo AML patients, 31 patients at complete remission (CR) time, 8 patients at relapse time and 30 normal controls. Results MiR-17 was upregulated in de novo AML compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Our data is similar to Bomben et al’s results who demonstrated significantly higher expression levels of miR-17-5p in ZAP-70-positive CLL patients [ 39 ]. In addition, miR-17-5p has been shown to be overexpressed in acute myeloid leukemia and could be considered as an independent negative prognostic factor [ 40 ]. On the other hand, Moussay et al found that levels of circulating miR-20a-5p correlated with the disease stage, which was similar to the value obtained using ZAP-70 directly [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data is similar to Bomben et al’s results who demonstrated significantly higher expression levels of miR-17-5p in ZAP-70-positive CLL patients [ 39 ]. In addition, miR-17-5p has been shown to be overexpressed in acute myeloid leukemia and could be considered as an independent negative prognostic factor [ 40 ]. On the other hand, Moussay et al found that levels of circulating miR-20a-5p correlated with the disease stage, which was similar to the value obtained using ZAP-70 directly [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in MLL, where the abovementioned miRNAs are overexpressed, targeting both miR-17-5p and miR-19a-3p by antagomiRs reduces the ability of MLL cells to form colonies compared to non-MLL AML controls [58]. Several other studies suggested that the miR-17 cluster is associated with a poor prognosis [33,59] through several mechanisms, including the promotion of leukemic blast proliferation [60]. With regard to macrophage polarization, miR-17 and miR-20a promote an M1 phenotype by inhibiting signal-regulatory protein a (SIRPa) [60].…”
Section: Micrornas Associated With a Bad Prognosis Of Aml And M1 Pola...mentioning
confidence: 97%
“…Many reports presented the association between miRNA expression and specific chromosomal abnormalities [26,27] or mutations in AML [28][29][30]. On the other hand, miRNAs were also associated with prognosis, disease progression, or proliferation [31][32][33][34]. Based on these findings, miRNAs are now regarded as important biomarkers that might predict the response to treatment, the risk of progression, or the rate of complete remission (CR) and overall survival (OS) in both solid cancers of hematological malignancies [35][36][37][38].…”
Section: Mirnas and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Ostrovsky et al observed that multiple SNPs in HPSE were significantly associated with hematological malignancies, including acute myeloid leukemia (AML) [52]. Cao et al recently proposed that the miRNA miR-17 was associated with AML and served as an independent prognostic factor of AML survival; HPSE was detected as one of the miR-17 targets [53]. A differential expression analysis was conducted on the independent testing dataset GSE15061 by GEO2R [54].…”
Section: Leukemia Associations Of Dark Biomarkersmentioning
confidence: 99%